Meje rasti in meje privatizacije - Kirn, Andrej (Teorija in praksa, 2007)
Eco-physical limits to economic growth and social consequences of not taking them into account and exceeding them are theoretically and empirically more defined than the limits to privatization. In principal neutral position for or against privatization is in theory possible, but it is impossible in political practice. Successfulness of public service depends on effectiveness of the state regulation. Limits to growth and limits to privatization are interrelated to the extent to that accelerated growth depends on private property form and that the limits to growth demand changes in property relations.
Keywords: Economic growth; Ekonomska rast; Economic policy; Ekonomska politika; Privatizacija; Privatization; Meje; Boundaries; Democracy; Demokracija; Regulacija; Regulation; Ideologija; Ideology; Družbeni vidik; Social aspects